Unexpected stability of the iron(II) complex by an asymmetrical Schiff base from Fe(III): structure, magnetic and Mössbauer investigations - Dawit Tesfaye; Mamo Gebrezgiabher; Jonas Braun; Taju Sani; Sebastien Diliberto; Pascal Boulet; Nandakumar Kalarikkal; Christopher E. Anson; Annie K. Powell; Madhu Thomas (Royal Society Open Science)
The asymmetric Schiff base prepared in situ from ethylenediamine and pyridine-2-carboxaldehyde reacts with Fe(ClO4)3·6H2O to form the Fe(II) complex [FeL2](ClO4)2 with L = N,N-diethyl-N′-(pyridin-2-yl)methylene)ethane-1,2-diamine, where the Fe(III) starting material has been unexpectedly reduced to Fe(II). This complex was characterized by elemental analysis, infrared spectra, single crystal and powder X-ray diffraction measurements, variable temperature DC magnetic measurement and room temperature Mössbauer spectroscopy. The asymmetric ligand L coordinates in a tridentate fashion through its pyridyl, azomethine and amino nitrogen atoms, generating a distorted octahedral geometry around the central metal ion. Variable temperature magnetic studies and a Mössbauer measurement show that the iron is locked in the low spin Fe(II) states.